Cross-Border and Local Cooperation on the island of Ireland - A Behavioural Perspective - Stephen Roper (European Regional Science Association (ERSA), 2005)
There is now general agreement that inter-firm cooperation through networks, partnerships and supply-chains can, by facilitating knowledge exchange and reducing transaction costs, contribute both to innovation and company competitiveness. Dense patterns of 'association', reinforced by links between firms and other support institutions, have also been linked to cluster and regional growth. Case-studies of areas with high levels of co-operation have been characterised by social and economic uniformity, geographical contiguity, high levels of social capital (i.e. trust) and stable and supportive governance and support institutions. Border regions are often characterised by exactly the opposite conditions: poor infrastructure, low population and business densities, low levels of social capital and governance which is at best divided, and at worst, antagonistic. In this context, cross-border cooperation can play an important role, countering the structural discontinuity of border regions and generating a potentially positive growth dynamic In terms of the Northern Ireland-Ireland border the general socio-economic difficulties of border areas have been exacerbated by violent social and political unrest. Although the security situation has been more stable in recent years, the economic and social legacy of the past persists. In this context, cross-border co-operation has been seen as one way in which past divisions can be healed and an integrated all-island economy developed. The aims of this paper are two-fold. First, to augment the relatively limited empirical literature on the economic determinants of the probability that firms will engage in cross-border cooperation. In particular, we adopt a transactions cost perspective and seek to identify those factors which are either specific to, or disproportionately important, in shaping the probability of cross-border interaction. The second objective is to contribute some positive evidence to the, all too often, opinion-driven debate on North-South cooperation on the island of Ireland. Specifically, we focus on identifying any differences in the determinants of cross-border co-operation in Ireland and Northern Ireland This provides some insight into current levels of co-operative activity as well as highlighting potential areas for policy intervention. The paper adopts a simultaneous probit approach to examining the determinants of cross-border and local cooperation between firms in Ireland and Northern Ireland. The conceptual approach draws on the transactions cost literature, arguing that firms will engage in cooperation where the costs involved are less than those of market interaction. Cross-border cooperation is modelled as an alternative – and possible complement or substitute – for local co-operative activity. The study is based on a large-scale interview survey conducted in 2002. The results identify a number of factors which help to predict the probability that a firm will engage in cross-border cooperation. Perhaps unsurprisingly it proves easier to predict cross-border cooperation by firms in Northern Ireland than in the larger and more buoyant, Ireland. The results also suggest some complementarity between local and cross-border co-operation, and a declining probability of cross-border cooperation the further a firm is located from the border. Somewhat surprisingly, however, no clear size or sectoral bias is found in the probability of engaging in cross-border cooperation.
Keywords: 330